'She is like my mother': Community-based care of drug-resistant tuberculosis in rural Eswatini. Issue 6 (3rd June 2021) - Burtscher, Doris; Juul Bjertrup, Pia; Vambe, Debrah; Dlamini, Velibanti; Mmema, Nqobile; Ngwenya, Siphiwe; Rusch, Barbara; Kerschberger, Bernhard
ABSTRACT: Patients with drug-resistant tuberculosis (DR-TB) have received community-based care in Eswatini since 2009. Trained and compensated community treatment supporters (CTSs) provide directly observed therapy (DOT), injectables and psychological support. We examined the acceptability of this model of care among DR-TB patients, including the perspective of family members of DR-TB patients and their CTSs in relation to the patient's experience of care and quality of life. This qualitative research was conducted in rural Eswatini in February 2018. DR-TB patients, CTSs and family members participated in in-depth interviews, paired interviews, focus group discussions and PhotoVoice. Data were thematically analysed and coded, and themes were extracted. Methodological triangulation enhanced the interpretation. All patients and CTSs and most family members considered community-based DR-TB care to be supportive. Positive aspects were emotional support, trust and dedicated individual care, including enabling practical, financial and social factors. Concerns were related to social and economic problems within the family and fears about infection risks for the family and the CTSs. Community-based DR-TB care was acceptable to patients, family members and CTSs. To reduce family members' fears of TB infection, information and sensitisation within the family and constant follow-up appear crucial.